Representasi Tokoh Raras Prayagung dalam Novel "Aroma Karsa" Karya Dee Lestari - Karina Salsabila; Rafi Zaidan Alamsyah (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
Aroma Karsa is a novel with a complex storyline, which combines various characters who play the role of heroes and villains, one of which is the character Raras Prayagung who has an obsession with a plant called Puspa Karsa. What is unique about the character of Raras Prayagung is his portrayal as a dark and gray figure. The purpose of this research will focus on the representation of the character of Raras Prayagung, then the role, function and contribution of Raras Prayagung in the plot of the story and identify the values and messages that can be learned through the character of Raras Prayagung in the novel Aroma Karsa. The method used in this research is descriptive qualitative because the data used in this research comes from words, sentences, or quotes found in the novel Aroma Karsa. The result of the research found is that Raras Prayagung is a character who has a complex characterization because it represents various things, including ambition, determination, sacrifice, and moral complexity.